The importance of technical analysis for improving performance in athletics in long distance running - Dobre, A.-G.; Mereuta, C.; Grigore, F.-E. (Annals of the University Dunarea de Jos Galati, Fascicle XV: Physical Education and Sport Management, 2019)
It is well known that the level at which the performances in the sports competitions have come lately is also due to the improvement of the specific techniques by: studying the most intimate / hidden aspects of the running technique that provide insight into the level of influence of the muscle chains involved in each phase of the movement; knowledge of the biomechanical details that can improve the technique of the general run and the departures from the start. It is assumed that participation in high-performance competitions is possible by restructuring the training efforts during the annual training cycle, using increased proportionate efforts in the mixed and anaerobic area as well as the approach as a separate indicator of the compensatory effort, and in this restructuring an essential role could be played by the technical aspect of long runs. When we discuss the technique of athletics, We must consider two aspects which, depending on how well they are improved, influence the final result. This is the sample technique and the treadmill technique.